A formação do professor perante o programa ler e escrever: mudanças e transformações - Bueno, Ivana Santiago (2016)
This research aims to investigate how and if it happens continuing education teacher in the school locus during the ATPC. Currently the teacher needs to learn of knowledge and concepts to re-establish a connection between knowing how to be and know relearn how to be a teacher, become. To do this, knowing mediate with the educational field to show in practice what the theory holds him filling his knowledge. This same theory based on several concepts that transmutes teacher "missionary" to become a teacher today (Assmann, 2007). Faced with this continuing education perspective this research is to study the formation of the teacher, the changes and possible changes to the READ AND WRITE PROGRAM.